Ophthalmic corticosteroids-related adverse events: the FDA adverse event reporting system (FAERS) database pharmacovigilance study - Chengzhi Liu; Xinyu Wang; Xusheng Cao (Frontiers in Pharmacology)
BackgroundCorticosteroids are extensively used in ophthalmology, particularly for treating various inflammatory conditions. Despite their effectiveness, prolonged or high-dose corticosteroid use is associated with significant adverse drug reactions (ADRs), such as increased intraocular pressure, cataract formation, and secondary infections. However, there is currently no systematic study comparing the side effects of ophthalmic corticosteroids. This study aims to investigate the safety profiles of ophthalmic corticosteroids through pharmacovigilance analysis using the FDA Adverse Event Reporting System (FAERS) database.MethodsWe conducted a retrospective analysis of ADR reports related to commonly used ophthalmic corticosteroids from the FAERS database, covering the period from Q1 2004 to Q4 2023. Clinical features such as gender, age, administration route, and dosage form were also analyzed. Signal detection methods, including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and the Multi-Item Gamma Poisson Shrinker (MGPS), were used to identify potential safety signals.ResultsA total of 9,854 ADRs related to ophthalmic corticosteroids were retrieved, with the most frequently reported drugs being Ozurdex (1,784 cases), Lotemax (3,239 cases), and Durezol (2,789 cases). Women accounted for a higher proportion of ADRs across most corticosteroids. ADR induction time analysis results showed that ADRs tend to occur in the early stages of drug use. The most common ophthalmic ADRs identified included eye inflammation, cataract, visual impairment, uveitis, eye pain, blurred vision, and retinal detachment. Additionally, Maxidex has been linked to endocrine disorders, while Ozurdex, Iluvien, and Triesence exhibited significant signals for product issues, likely related to their intraocular injection procedures. Notably, cataract was the most common PT among these drugs.ConclusionOur study reveals significant safety concerns related to using ophthalmic corticosteroids, particularly regarding adverse reactions that can impact visual function. These findings highlight the need for careful monitoring and individualized treatment plans to minimize the risk of ADRs in patients receiving corticosteroid therapy. Future studies combining FAERS data with large-scale clinical research are needed to explore these safety concerns further.